Regulation and characterization of the galactose-phosphoenolpyruvate-dependent phosphotransferase system in Lactobacillus casei. - Chassy, B M (1983)
Cells of Lactobacillus casei grown in media containing galactose or a metabolizable beta-galactoside (lactose, lactulose, or arabinosyl-beta-D-galactoside) were induced for a galactose-phosphoenolpyruvate-dependent phosphotransferase system (gal-PTS). This high-affinity system (Km for galactose, 11 microM) was inducible in eight strains examined, which were representative of all five subspecies of L. casei. The gal-PTS was also induced in strains defective in glucose- and lactose-phosphoenolpyruvate-dependent phosphotransferase systems during growth on galactose. Galactose 6-phosphate appeared to be the intracellular inducer of the gal-PTS. The gal-PTS was quite specific for D-galactose, and neither glucose, lactose, nor a variety of structural analogs of galactose caused significant inhibition of phosphotransferase system-mediated galactose transport in intact cells. The phosphoenolpyruvate-dependent phosphorylation of galactose in vitro required specific membrane and cytoplasmic components (including enzyme IIIgal), which were induced only by growth of the cells on galactose or beta-galactosides. Extracts prepared from such cells also contained an ATP-dependent galactokinase which converted galactose to galactose 1-phosphate. Our results demonstrate the separate identities of the gal-PTS and the lactose-phosphoenol-pyruvate-dependent phosphotransferase system in L. casei.